Research on mechanical properties of Bacillus subtilis biofilm expressing TasA-n16N - QIN Simin; LIU Suying; ZHU Ying; LYU Min (He jishu, 2022)
BackgroundBacterial biofilm is a structure formed by bacteria communities living in a self-produced matrix of extracellular polymeric substances (EPS) composed of polysaccharides, proteins, nucleic acids, and so on. In the field of synthetic biology, bacterial biofilms can be transformed into variable active functional materials by regulating the expression of specific bacterial proteins with different gene circuits. However, the weak mechanical properties of bacterial biofilms limit the application of these materials in wearable devices, coatings and building materials. [Propose] This study aims to investigate the effect of expression of fusion protein to the mechanical property of bacterial biofilm, and the non-opportunistic pathogen Bacillus subtilis was selected as model strain.MethodsThe engineering bacterial biofilm was prepared as a block gel by traditional calcium carbonate mineralization method. After characterization with synchrotron radiation X-ray transmission microscope, scanning electron microscope (SEM) and transmission electron microscope (TEM), the mechanical property of the original biofilm and biofilm gel was studied by rheological analysis.ResultsResults of rheological test show that slight increase of the storage modulus is discovered, indicating the enhancement of the mechanical property of biofilm block gel, and the bacterial structure inside the biofilm is complete and remains active.ConclusionsThis study provides a new idea for the biomimetic mineralization of bacterial biofilms and the design and preparation of active functional materials.